Investigation of blasting parameters to optimize fragmentation - O. Dojcar (The Institute of Materials, Minerals and Mining, 1991)
The results of a laboratory investigation of rock fragmentation conducted with a model material were partially verified under field conditions. The object of the investigation was to study the qualitative and quantitative relations between the parameters of the primary blast and fragmentation to enable the planning of an economically efficient degree of disintegration with optimum utilisation of the blast energy. The three blast parameters that were considered were burden, specific charge and the ratio of spacing to burden